Identity Conflicts In Nigeria: Historical Perspectives And Contemporary Implications - Berebon, Charles (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
Nigeria, the most populous country in Africa, is characterized by a complex tapestry of ethnic, religious, and regional identities. This study examines the roots and dynamics of identity conflicts in Nigeria, focusing on historical antecedents and contemporary manifestations. It explores the intricate interplay between major and minor ethnic groups, the role of religion in conflict mobilization, and the socio-political implications of these conflicts. Using the Plateau North Senatorial District, specifically Jos North Local Government Area, as a case study, the research delves into the historical relationships between the Hausa/Fulani and minority ethnic groups, the impact of colonial and post-colonial state formation, and the recurring patterns of conflict and displacement. Through a combination of historical analysis and field research, this study aims to provide a comprehensive understanding of the persistent identity conflicts in Nigeria and suggest pathways for conflict resolution and sustainable peace.